LAMA PEMAKAIAN POPOK SEKALI PAKAI DAN TEKNIK PERSONAL HYGIENE MEMPENGARUHI TERJADINYA INFEKSI SALURAN KEMIH PADA ANAK YANG DIRAWAT DI RUANG NUSA INDAH DR. R SOSODORO DJATIKOESOEMO BOJONEGORO TAHUN 2014 - Wiwik Utami, Wiwik Utami (AKADEMI KESEHATAN RAJEKWESI BOJONEGORO, 2014)
Today, it could facilitate the use of Pampers parents when they are traveling with children or while sleeping at night. However, the use of Pampers baby that is too often also be bad for children's health, the risk of Urinary Tract Infection (UTI). The purpose of the study analyzed the long wearing Pampers and personal hygiene techniques on the incidence of urinary tract infection. Observational study design with a cross-sectional approach. The study population of all children aged 0-3 years wearing Pampers treated at the General Hospital dr.R Sosodoro Djatikoesoemo Bojonegoro wiith consecutive sampling. Independent variable is the time use Pampers and personal hygiene techniques, while the dependent variable urinary tract infection. Data retrieval independent variables with the dependent variable while the Q & A with the examination of the urine. After the data collected is done editing, coding, scoring and tabulated to determine the percentage. The results were analyzed by descriptive and statistical test followed by Chy scuare with p <0.05. The results of the 36 respondents indicated most respondents more than 3 hours of wearing Pampers 32 (94.5%) of respondents and most personal techniques too bad hygienenya 28 ((79%). However the incidence of UTI only only 10 respondents. With statistical chy Square test especially Fisher's Exact Test was obtained significance value (p) = 0, 543> ? = 0.05. Ho is accepted, meaning no use Pampers long relationship with UTI, as well as personal hygiene variables with the incidence of UTI with chy Square statistical test especially Fisher's Exact Test was obtained significance value (p) = 1, 000> ? = 0.05. H0 is accepted, it means that there is no relationship with UTI personal hygiene. In conclusion there is no relationship between the duration of use pemper and personal hygiene on the incidence of urinary tract infections in children admitted to Nusa Indah ward Sosodoro Djatikusump hospital Bojonegoro 2014 Advice to mothers of infants under five years in order to replace Pampers not wait for the full first and with personal hygiene techniques that right to prevent urinary tract infections.Keywords: Pampers, personal hygiene, urinary tract infection.